PENGARUH DISIPLIN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT BPR DANA CENTRAL MULIA - Chang, Dennis; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to identify the influence of work discipline and incentive variables on employee performance at PT BPR Dana Central Mulia. The research method used is quantitative approach, data analysis using SPSS version 25 software program. Collection techniques the data was conducted by distributing questionnaires to 112 respondents. The results showed partially good as well as simultaneously variables of work discipline and incentives affect the performance of employees of PT BPR Dana Central Mulia. The implication of the results of this study is that to improve performance employees of PT BPR Dana Central Mulia can be done by increasing discipline and better incentives.